Laminate, bag for solid-state batteries, all-solid-state battery, and diaphragm pump
A laminated body with fluorine resin layers and a metal layer addresses the barrier and heat resistance issues in all-solid batteries and diaphragm valves, ensuring reliable operation and durability.
Patent Information
- Application Number
- JP2024116247
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-03-06
- Filing Date
- 2024-07-19
- Publication Date
- 2025-02-05
AI Technical Summary
Existing battery packaging materials lack sufficient barrier and heat resistance to protect all-solid batteries, which require high temperature operation, and diaphragm valves in diamond pumps need improved durability and resistance to fluids.
A laminated body composed of a first fluorine resin layer with adhesive functional groups, a metal layer, and a second fluorine resin layer, providing excellent barrier and heat resistance, is used for battery exteriors and diaphragm valves.
The laminated body maintains battery characteristics and prevents peeling at high temperatures, ensuring effective charging and discharging, and enhances the durability of diaphragm valves.
Smart Images

Figure 2025017342000003 
Figure 2025017342000004 
Figure 2025017342000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate, a bag for a solid-state battery, an all-solid-state battery, and a diaphragm pump. Regarding. [Background technology]
[0002] Packaging materials for batteries are described in Patent Documents 1 and 2. Such battery packaging materials are desired to have barrier properties that make it difficult for water vapor, oxygen, and the like to pass through. The packaging material described in Patent Document 1 is a packaging material for polymer batteries, and describes a laminate in which a barrier layer and an outermost layer composed of an oriented polyester resin or an oriented polyamide resin are laminated via an adhesive layer. The packaging material described in Patent Document 2 is a packaging material for cases of lithium ion secondary batteries, in which a biaxially oriented polyamide film layer is laminated integrally onto the upper surface of an aluminum foil layer via a urethane resin adhesive, and a thermoplastic resin unoriented film layer is laminated integrally onto the lower surface of the aluminum foil layer via a maleic anhydride modified polypropylene layer or an unmodified polypropylene layer.
[0003] Also, Patent Document 3 describes a diaphragm valve in which a heat-resistant reinforcing cloth is embedded in a valve body made of fluororesin. The diaphragm valve provided in the diaphragm pump is displaced by air pressure to control the movement of the fluid. In Patent Document 3, polytetrafluoroethylene is used as the fluororesin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-138793 A [Patent Document 2] JP 2013-65565 A [Patent Document 3] Japanese Patent Application Publication No. 61-215050 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, research into all-solid-state batteries as an alternative to lithium-ion secondary batteries has progressed, with two main types being considered: sulfide-based and oxide-based all-solid-state batteries. Both sulfide-based and oxide-based all-solid-state batteries can operate at higher temperatures than lithium-ion secondary batteries, so there is a demand for more heat-resistant exteriors for all-solid-state batteries. Diaphragm valves are also required to have excellent barrier properties and heat resistance.
[0006] An object of one embodiment of the present disclosure is to provide a laminate having excellent barrier properties and heat resistance, and a pouch for an all-solid-state battery, an all-solid-state battery, and a diaphragm pump using the laminate. [Means for solving the problem]
[0007] The present disclosure includes the following aspects. <1> A laminate having, in this order, a first fluororesin layer containing a fluororesin having an adhesive functional group, a metal layer having an average thickness of 5 to 300 μm, and a second fluororesin layer containing a fluororesin having an adhesive functional group. <2> the adhesive functional group is at least one selected from the group consisting of a carbonyl group-containing group, a hydroxy group, an epoxy group, an amide group, an amino group, an isocyanate group, a glycidyl group, a cyano group, a silyl group, and a silanate group; <1> The laminate according to claim 1. <3> The fluororesin having an adhesive functional group in the first fluororesin layer and the second fluororesin layer each independently contains a unit derived from ethylene and a unit derived from tetrafluoroethylene. a copolymer having a unit derived from ethylene and a unit derived from a monomer having an adhesive functional group, a copolymer having a unit derived from tetrafluoroethylene, a unit derived from a perfluoro(alkyl vinyl ether), and a unit derived from a monomer having an adhesive functional group, a copolymer having a unit derived from vinylidene fluoride and a unit derived from a monomer having an adhesive functional group, and a copolymer having a unit derived from vinyl fluoride and a unit derived from a monomer having an adhesive functional group, <1> or <2> The laminate according to claim 1. <4> The metal layer comprises at least one selected from the group consisting of aluminum, an aluminum alloy, stainless steel, copper, and steel; <1> ~ <3> 13. The laminate according to claim 12 . <5> and an outer layer containing at least one resin selected from the group consisting of a fluororesin other than the fluororesin having an adhesive functional group, a polyimide, and a polyether ether ketone, on the outer side of at least one of the first fluororesin layer and the second fluororesin layer. <1> ~ <4> 13. The laminate according to claim 12 . <6> The other fluororesin includes at least one selected from the group consisting of a copolymer having a unit derived from ethylene and a unit derived from tetrafluoroethylene, a copolymer having a unit derived from tetrafluoroethylene and a unit derived from perfluoro(alkyl vinyl ether), a polymer having a unit derived from vinylidene fluoride, and a polymer having a unit derived from vinyl fluoride. <5> The laminate according to claim 1. <7> An exterior body for a battery, <1> ~ <6> 13. The laminate according to any one of claims 1 to 12. <8> An exterior body for all-solid-state batteries. <1> ~ <7> 13. The laminate according to claim 12 . <9> It is a diaphragm valve. <1> ~ <6> 13. The laminate according to claim 12 . <10> One or more <1> ~ <6> 13. A pouch for an all-solid-state battery, comprising the laminate according to claim 12, at least a portion of a periphery of which is heat-sealed. <11> An all-solid-state battery cell and an exterior packaging for the all-solid-state battery cell <1> ~ <6> and the laminate according to any one of the preceding claims. <12> <1> ~ <6> 13. A diaphragm pump having a diaphragm valve including the laminate according to any one of claims 1 to 12. Effect of the Invention
[0008] According to one embodiment of the present disclosure, it is possible to provide a laminate having excellent barrier properties and heat resistance, and a pouch for an all-solid-state battery, an all-solid-state battery, and a diaphragm pump using the laminate. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a laminate according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of a laminate according to the present disclosure. [Diagram 3] FIG. 1 is a perspective view showing an example of an exterior body of an all-solid-state battery which is an application of the pouch of the present disclosure, and an example of the all-solid-state battery of the present disclosure. [Figure 4] 1 is a photograph showing the appearance after a charge-discharge test when the laminate of Example 6 was used as an exterior body. [Diagram 5] 1 is a photograph showing the appearance after a charge-discharge test when the laminate of Example 1 is used as an exterior body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, the amount of each component is particularly limited when there are multiple substances corresponding to each component. Unless otherwise specified, the total amount of multiple substances. In the present disclosure, the term "fluororesin" refers to a resin having fluorine atoms in the molecule. In this disclosure, the term "unit" refers to a portion derived from a monomer that exists in a polymer and constitutes the polymer. The term "unit" also refers to a unit that is obtained by chemically converting the structure of a unit after the formation of a polymer. In some cases, units derived from individual monomers are referred to by the name of the monomer with "unit" added. The average thickness of each layer is the thickness at room temperature (25°C), and is measured using a high-precision digital micrometer MDH-25MB manufactured by Mitutoyo Corporation, and is the average of the measurements obtained at any five points. value.
[0011] <Laminate> The laminate of the present disclosure comprises, in this order, a first fluororesin layer containing a fluororesin having an adhesive functional group, a metal layer having an average thickness of 5 to 300 μm, and a second fluororesin layer containing a fluororesin having an adhesive functional group. The laminate having the above-mentioned structure has excellent barrier properties and heat resistance, the reason for which is presumed to be as follows.
[0012] The use of a metal layer with an average thickness of 5 to 300 μm provides excellent barrier properties, and the provision of layers containing a fluororesin on both sides of the metal layer provides excellent heat resistance. In particular, it is presumed that the fluororesin has adhesive functional groups, which provide excellent adhesion to the metal layer, and prevents the layer containing the fluororesin from peeling off from the metal layer even when the laminate is heated. When a laminate having such properties is used as an exterior body for a battery, particularly an all-solid-state battery, the battery tends to have excellent barrier properties and heat resistance even during repeated charging and discharging from low temperatures to high temperatures, and the battery properties such as charge and discharge capacity are likely to be maintained. Furthermore, since the laminate of the present disclosure has excellent barrier properties and heat resistance, it is also useful as a diaphragm valve for a diaphragm pump.
[0013] In addition, in the battery packaging materials described in Patent Documents 1 and 2, a non-fluorinated resin layer is provided on the barrier layer via an adhesive layer. In general, it takes about one week to cure the adhesive layer. However, the laminate of the present disclosure does not require an adhesive layer because the first fluorinated resin layer and the second fluorinated resin layer contain a fluorinated resin having an adhesive functional group. Therefore, the laminate of the present disclosure is also excellent in productivity. Each layer of the laminate will now be described.
[0014] [First fluororesin layer and second fluororesin layer] The first fluororesin layer and the second fluororesin layer each contain a fluororesin having an adhesive functional group (hereinafter also referred to as "fluororesin (A)").
[0015] In the present disclosure, the term "fluororesin having adhesive functional groups" does not include cases in which the adhesive functional groups are derived from a polymerization initiator or a chain transfer agent and are present only at the terminals.
[0016] The fluororesin (A) contained in the first fluororesin layer and the second fluororesin layer may be the same or different. From the viewpoint of easy production of the laminate, it is preferable that the fluororesin (A) contained in the first fluororesin layer and the second fluororesin layer is the same, but it is preferable to appropriately select it according to the requirements for the part where the laminate is arranged. The fluororesin (A) contained in the first fluororesin layer may be of one type alone or in combination of two or more types. The fluororesin (A) contained in the second fluororesin layer may be of one type alone or in combination of two or more types.
[0017] The melting point of the fluororesin (A) is preferably 160° C. or higher, more preferably 170° C. or higher. In the present disclosure, "melting point" means the temperature corresponding to the maximum value of the melting peak measured by differential scanning calorimetry (DSC). When the melting point of the fluororesin (A) is equal to or higher than the lower limit of the above range, deterioration of the first fluororesin layer and the second fluororesin layer is suppressed when exposed to high temperatures (e.g., 150°C or higher), and peeling from the metal layer is less likely to occur when exposed to high temperatures.
[0018] When the heat resistance of the laminate is important, such as for application to a diaphragm valve, the melting point of the fluororesin (A) is preferably 200° C. or higher, more preferably 250° C. or higher, and even more preferably 280° C. or higher.
[0019] The melting point of the fluororesin (A) is preferably 350°C or lower, more preferably 320°C or lower. From the viewpoint of improving the heat sealability of the laminate, the melting point of the fluororesin (A) is preferably 300°C or lower, more preferably 280°C or lower, and more preferably 250°C or lower. If the melting point of the fluororesin (A) is equal to or lower than the upper limit of the above range, the fluororesin can be laminated with the metal layer at a relatively low temperature, and the first fluororesin layer and the second fluororesin layer can be heat-sealed. Therefore, for example, when another outer layer is provided on the outside of at least one of the first fluororesin layer and the second fluororesin layer, deformation of the outer layer due to heating during production is suppressed, and wrinkles and breakage of the laminate are suppressed.
[0020] The adhesive functional group may be at least one selected from the group consisting of a carbonyl group-containing group, a hydroxy group, an epoxy group, an amide group, an amino group, an isocyanate group, a glycidyl group, a cyano group, a silyl group, and a silanate group. Examples of the carbonyl group-containing group include a group having a carbonyl group between carbon atoms of a hydrocarbon group, a carbonate group, a carboxy group, a haloformyl group, an alkoxycarbonyl group, a carboxy ester group, and an acid anhydride group. The adhesive functional group is preferably a carboxy group or an acid anhydride group from the viewpoint of excellent adhesiveness.
[0021] The adhesive functional group possessed by the fluororesin (A) may be derived from a monomer having an adhesive functional group, or may be further present in a terminal group derived from a polymerization initiator or a chain transfer agent. The adhesive functional group of the fluororesin (A) may be introduced by a surface treatment, such as a known method including a corona discharge treatment and a plasma treatment (excluding the corona discharge treatment). The content of adhesive functional groups in the fluororesin (A) is 1 × 10 6 The number of particles is preferably 100 to 50,000, and more preferably 500 to 10,000. The proportion of units derived from a monomer having an adhesive functional group relative to all units in the fluororesin (A) is preferably from 0.01 to 5 mol %, particularly preferably from 0.05 to 1 mol %.
[0022] From the viewpoints of excellent adhesion and excellent formability into films, etc., the fluororesin (A) preferably contains at least one selected from the group consisting of a copolymer having units derived from ethylene, units derived from tetrafluoroethylene, and units derived from a monomer having an adhesive functional group (hereinafter also referred to as "adhesive ETFE"), a copolymer having units derived from tetrafluoroethylene, units derived from perfluoro(alkyl vinyl ether), and units derived from a monomer having an adhesive functional group (hereinafter also referred to as "adhesive PFA"), a copolymer having units derived from vinylidene fluoride and units derived from a monomer having an adhesive functional group, and a copolymer having units derived from vinyl fluoride and units derived from a monomer having an adhesive functional group. The fluororesin (A) is preferably at least one selected from the group consisting of adhesive ETFE and adhesive PFA.
[0023] The monomer having an adhesive functional group is preferably a monomer having a carboxy group, an acid anhydride group, or a carboxylic acid halide group, and more preferably an unsaturated dicarboxylic acid anhydride. Examples of the unsaturated dicarboxylic acid anhydride include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride (himic anhydride), and maleic anhydride. The monomer having an adhesive functional group may have one type of adhesive functional group alone, or may have two or more types of adhesive functional groups.
[0024] The adhesive ETFE may contain units derived from other monomers than ethylene, TFE, and monomers having adhesive functional groups, as necessary. Examples of other monomers include fluoroolefins (excluding tetrafluoroethylene), fluoro(alkyl vinyl ether), etc. The adhesive PFA may contain units derived from other monomers than TFE, perfluoro(alkyl vinyl ether), and monomers having adhesive functional groups, as necessary. Examples of other monomers include fluoroolefins (excluding tetrafluoroethylene).
[0025] Specific examples of adhesive ETFE include the "fluororesin having functional groups" described in WO 2006 / 134764, the "adhesive functional group-containing fluororesin" described in JP 2012-106494 A, and the "fluorine-containing ethylenic polymer having carbonyl groups" described in WO 2001 / 058686.
[0026] Specific examples of adhesive PFA include "PFA having functional group i" described in WO 2019 / 203243.
[0027] The first fluororesin layer and the second fluororesin layer may contain components other than the fluororesin (A) as long as the effects of the present disclosure are not impaired. Examples of other components include known resin additives, fluororesin having no adhesive functional group (hereinafter also referred to as "fluororesin (B)"), polyamide, amino group-containing polymer, fluorine-containing elastomer (fluororubber having VDF units, fluororubber having propylene units and TFE units, etc.) and crosslinked products thereof, resin particles (polytetrafluoroethylene particles, polyether ether ketone particles, polyphenylene sulfide particles, etc.), and the like.
[0028] In addition, "fluororesin with no adhesive functional groups" refers to a fluororesin that does not have any adhesive functional groups at all, or has a main chain carbon number of 1×10 6 This refers to fluororesin having 50 or less particles per unit.
[0029] Examples of the fluororesin (B) include a copolymer having units derived from ethylene and units derived from tetrafluoroethylene (hereinafter referred to as "ETFE"), a copolymer having units derived from TFE and units derived from perfluoro(alkyl vinyl ether) (hereinafter referred to as "PFA"), a polymer having units derived from vinylidene fluoride (hereinafter referred to as "PVDF"), and a polymer having units derived from vinyl fluoride (hereinafter referred to as "PVF").
[0030] The proportion of the fluororesin (A) in each of the first fluororesin layer and the second fluororesin layer is preferably 5 to 100 mass%, more preferably 20 to 100 mass%, and even more preferably 50 to 100 mass%, of the materials constituting the layers (100 mass%). When the ratio of the fluororesin (A) in the first fluororesin layer and the second fluororesin layer is at least the lower limit of the above range, the adhesion and heat resistance are further excellent.
[0031] The average thickness of the first fluororesin layer and the second fluororesin layer is preferably 1 to 200 μm, more preferably 1 to 100 μm, and even more preferably 5 to 10 μm. When the average thickness of the first fluororesin layer and the second fluororesin layer is equal to or greater than the lower limit of the above range, the heat resistance is more excellent. When the average thickness of the first fluororesin layer and the second fluororesin layer is equal to or less than the upper limit of the above range, the flexibility of the laminate is excellent.
[0032] [Metal layer] The laminate of the present disclosure has a metal layer. The metal layer preferably contains at least one selected from the group consisting of aluminum, aluminum alloy, stainless steel, copper, and steel, and more preferably contains at least one selected from the group consisting of aluminum, aluminum alloy, and stainless steel from the viewpoints of barrier properties, corrosion resistance, etc., and further preferably contains aluminum. The aluminum content in the metal layer is preferably 50 mass% or more, more preferably 80 mass% or more, further preferably 90 mass% or more, particularly preferably 95 mass% or more, and may be 100 mass%.
[0033] The water vapor permeability of the metal layer is 1g / m 2 ·day or less is preferable, 0.1g / m 2 ·day or less is preferable, 0.01g / m 2 ·days or less is even better. The water vapor permeability is measured using a differential pressure gas / water vapor permeability tester (GC method) at 40℃ RH90% based on JIS K7129-1:2019.
[0034] The oxygen permeability of the metal layer is 1 g·ml / m 2 ·day·atm or less is preferable, and 0.1g·ml / m 2 ·day·atm or less is preferable, and 0.01g·ml / m 2 ·day·atm or less is even more preferable. The oxygen permeability is measured at 23°C using a differential pressure gas / water vapor permeability tester (GC method) based on JIS K7126-2:2006.
[0035] The metal layer may be in the form of a metal foil or a vapor-deposited metal film.
[0036] The average thickness of the metal layer is 5 to 300 μm, preferably 5 to 100 μm, and more preferably 10 to 100 μm. When the average thickness of the metal layer is equal to or greater than the lower limit of the above range, the barrier property is more excellent. When the average thickness of the metal layer is equal to or less than the upper limit of the above range, the flexibility of the laminate is excellent.
[0037] Since the first fluororesin layer and the second fluororesin layer contain a fluororesin (A) having an adhesive functional group and have excellent adhesive properties, the metal layer may or may not be surface-treated.
[0038] [Outer layer] An outer layer may be provided on the outside of at least one of the first fluororesin layer and the second fluororesin layer. The outer layer preferably contains at least one resin selected from the group consisting of fluororesins other than the fluororesin having an adhesive functional group, polyimide, and polyether ether ketone. The other fluororesin includes fluororesin (B).
[0039] When the heat resistance of the laminate is important, such as in applications to diaphragm valves, the melting point of the other fluororesin is preferably 200° C. or higher, more preferably 250° C. or higher, and even more preferably 280° C. or higher.
[0040] The outer layer may contain components other than the resin as long as the effects of the present disclosure are not impaired. Examples of other components include known resin additives, resin particles, inorganic fillers, and the like.
[0041] The proportion of the resin in the outer layer is preferably 5 to 100 mass %, more preferably 20 to 100 mass %, and even more preferably 50 to 100 mass %, of the materials constituting the layer (100 mass %).
[0042] The average thickness of the outer layer on both the first fluororesin layer side and the second fluororesin layer side is preferably from 1 to 200 μm, more preferably from 1 to 100 μm, and further preferably from 5 to 100 μm, independently of each other. When the average thickness of the outer layer is equal to or greater than the lower limit of the above range, the outer layer is likely to exhibit its function, and when the average thickness of the outer layer is equal to or less than the upper limit of the above range, the flexibility of the laminate is excellent.
[0043] [Layer composition] 1 is a cross-sectional view showing an example of a laminate of the present disclosure. The laminate 10 includes a first fluororesin layer 12, a metal layer 14, and a second fluororesin layer 16, in this order.
[0044] The combination of materials constituting each layer is as follows. Layer containing adhesive ETFE (1) / Aluminum layer or aluminum alloy layer / Layer containing adhesive ETFE (1) Layer containing adhesive ETFE (1) / Aluminum layer or aluminum alloy layer / Layer containing adhesive ETFE (2) Layer containing adhesive PFA (1) / aluminum layer or aluminum alloy layer / layer containing adhesive PFA (1) Layer containing adhesive PFA (1) / Aluminum layer or aluminum alloy layer / Layer containing adhesive PFA (2) Layer containing adhesive ETFE (1) / Aluminum layer or aluminum alloy layer / Layer containing adhesive PFA (1)
[0045] Here, both adhesive ETFE (1) and adhesive ETFE (2) contain units derived from ethylene, TFE, and a monomer having an adhesive functional group, but differ in the content of each unit, the presence or absence of units derived from other monomers, or both the content of each unit and the presence or absence of units derived from other monomers. Both adhesive PFA (1) and adhesive PFA (2) contain units derived from TFE, perfluoro(alkyl vinyl ether), and a monomer having an adhesive functional group, but differ in the content of each unit, the presence or absence of units derived from other monomers, or both the content of each unit and the presence or absence of units derived from other monomers.
[0046] Fig. 2 is a cross-sectional view showing another example of the laminate of the present disclosure. The laminate 20 includes a first outer layer 21, a first fluororesin layer 22, a metal layer 24, a second fluororesin layer 26, and a second outer layer 27, in this order. Although the first outer layer 21 and the second outer layer 27 are provided in Fig. 2, only one of them may be provided.
[0047] The combination of materials constituting the first fluororesin layer 22, the metal layer 24, and the second fluororesin layer 26 is similar to the combination of materials constituting the first fluororesin layer 12, the metal layer 14, and the second fluororesin layer 16 in FIG. 1. The first outer layer 21 and the second outer layer 27 in the laminate 20 can contain the resins described above for the outer layers, and can further contain other components, etc., as necessary.
[0048] [Method for producing laminate] The laminate of the present disclosure may be produced by a method of hot pressing each layer formed into a film onto a metal layer (thermal lamination method), a method of applying a liquid containing the fluororesin (A) onto a metal layer, a method of coating the metal layer with the fluororesin (A) by electrostatic powder coating, or a combination of two or more of these methods. The same applies to the method of providing the outer layer.
[0049] Alternatively, a pre-laminate of two or three adjacent layers may be produced, and another layer may be formed on one or both sides of the pre-laminate to produce the laminate of the present disclosure. Furthermore, two types of pre-laminates may be produced, and the laminate of the present disclosure may be produced by laminating them. The pre-laminate may be produced by the same method as above.
[0050] [Application] INDUSTRIAL APPLICABILITY The laminate of the present disclosure has excellent barrier properties and heat resistance, and therefore can be suitably used for exterior bodies for batteries, in particular exterior bodies for all-solid-state batteries, diaphragm valves, and the like. In addition, the laminate of the present disclosure can be used as an exterior body for various batteries, not limited to all-solid-state batteries. Specific examples of batteries include, but are not limited to, semi-solid batteries (e.g., gel polymer type semi-solid batteries, clay type semi-solid batteries, liquid-added semi-solid batteries, etc.), lithium ion batteries (e.g., lithium sulfur batteries (Li-S batteries), lithium manganese iron phosphate batteries (LMFP batteries), lithium iron phosphate ion batteries (e.g., "M3P batteries" manufactured by Contemporary Amperex Technology Co., Ltd. (CATL)), coagulated batteries, all-resin batteries, and solar cells. The laminate of the present disclosure can also be used as a member such as a tab lead or a separator in the various batteries described above. The laminate of the present disclosure can also be used as an adhesive layer for components in the various batteries described above. The laminate of the present disclosure can also be used as an exterior material for power generating elements such as ambient elements, Peltier elements, and Seebeck elements. The laminate of the present disclosure can also be suitably used for other applications, such as battery electrodes, insulating members, insulating tubes, insulating films for motors, covering materials for motor windings, wrapping films for metal wires, capacitors, electronic substrates, semiconductor members, protective materials for semiconductor wafers, protective films, semiconductor device members, heat dissipation members, antistatic protective materials, semiconductor release films, conveyor belts, tape substrates, medical packaging materials, packaging materials for pharmaceuticals, packaging materials for medical instruments, packaging materials for sterilization treatment, medical tubes, sheets for aerospace exteriors, sheet packaging materials for food, food belts, electromagnetic wave shielding materials, heat shielding sheets, heat shielding plates, building materials, and building decorative materials.
[0051] <Battery exterior body> The laminate of the present disclosure may be an exterior body for a battery. The exterior body for a battery is not particularly limited as long as it is a body for exteriorly housing a battery, and may be a bag-shaped battery exterior body (hereinafter also referred to as a bag for a battery). A battery pouch using the laminate of the present disclosure can be obtained, for example, by heat-sealing part of the periphery of one or more laminates of the present disclosure to form a pouch. Examples of the form of the battery pouch include a three-sided sealed pouch formed by folding back and overlapping one sheet of the laminate of the present disclosure in the middle and heat-sealing the first layers of the peripheral edges of the overlapping three sides; and a four-sided sealed pouch formed by overlapping two sheets of the laminate of the present disclosure and heat-sealing the first layers of the peripheral edges of the overlapping four sides. A battery pouch using the laminate of the present disclosure can be used in all-solid-state batteries and the various batteries described above. Battery pouches are typically used for laminate-type and pouch-type battery cells, but battery pouches using the laminate of the present disclosure can be used for battery cells of various shapes, such as laminate-type, pouch-type, cylindrical, and rectangular.
[0052] <Exterior body for all-solid-state batteries> The laminate of the present disclosure may be an exterior body for an all-solid-state battery. The exterior body for an all-solid-state battery is not particularly limited as long as it is capable of exteriorly housing a battery, and may be a bag-shaped all-solid-state battery exterior body (hereinafter, referred to as an all-solid-state battery (also called a bag for use). The pouch for an all-solid-state battery of the present disclosure is formed by heat-sealing at least a portion of the periphery of one or more laminates of the present disclosure. The form of the pouch for an all-solid-state battery of the present disclosure may be the same as the form of the pouch for a battery described above.
[0053] 3 is a perspective view showing an example of an exterior body of an all-solid-state battery, which is an application of the pouch of the present disclosure. The pouch 30 is a three-sided sealed pouch formed by folding back and overlapping one laminate 10 midway and heat-sealing the periphery of the overlapping three sides to form seal portions 32 on the three sides.
[0054] Since the bag of the present disclosure is composed of the laminate of the present disclosure, it has excellent barrier properties and heat resistance, and is less likely to peel off at the sealed portions of the bag and at the interfaces between the layers of the bag when exposed to high temperatures.
[0055] <All-solid-state battery> The all-solid-state battery according to the present disclosure includes an all-solid-state battery cell and the laminate according to the present disclosure that covers the all-solid-state battery cell. The all-solid-state battery cell may be any of a sulfide-based cell, an oxide-based cell, and the like. The all-solid-state battery of the present disclosure is exterior-packaged with the laminate of the present disclosure, and therefore has excellent barrier properties and heat resistance, and is less susceptible to peeling at the seal portion of the laminate as an exterior package and at the interfaces between the layers of the laminate when exposed to high temperatures. As a result, the decrease in charge / discharge capacity when exposed to high temperatures is more suppressed than in the past.
[0056] The exterior of an all-solid-state battery cell using the laminate of the present disclosure can be seen in Fig. 3. The all-solid-state battery 40 has an all-solid-state battery cell 42 and a laminate 10 that exteriorizes the all-solid-state battery cell 42. The laminate 10 is formed by folding one sheet midway and overlapping it, and the edges of the three overlapping sides are heat-sealed. A positive electrode terminal 44 and a negative electrode terminal 46 protruding from an exterior body formed of the laminate 10 are sealed while being sandwiched between two sheets of the laminate 10.
[0057] <Diaphragm pump> The diaphragm pump of the present disclosure has a diaphragm valve including the laminate of the present disclosure. The diaphragm valve of the diaphragm pump of the present disclosure includes the laminate of the present disclosure, and therefore has excellent barrier properties and heat resistance. In addition, the diaphragm valve of the present disclosure has layers containing fluororesin on both sides of the metal layer, and therefore has excellent chemical resistance, and can be suitably used in a diaphragm pump that uses a solvent for pumping. The shape of the diaphragm valve is not particularly limited, and the central portion may be curved in an arc shape. EXAMPLES
[0058] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited thereto. Examples 1 to 5 are working examples, and Examples 6 to 9 are comparative examples.
[0059] [Example 1] (1-1) Preparation of ETFE film 1 ETFE1 was polymerized in the same manner as in Example 1 of WO 2015 / 182702, except that the ratio of TFE / E / CH2=CH(CF2)2F / itaconic anhydride was 58.5 / 39 / 2.0 / 0.3 (mol%). The melt flow rate of ETFE1 was 28 mm 3 / sec, and the melting point was 240°C. ETFE1 was extruded using a single-screw extruder with a screw diameter of 30 mm at a barrel temperature of 280°C and a die temperature of 300°C to produce pellets. The pellets were molded using a single-screw extruder with a screw diameter of 30 mm at a T-die temperature of 300°C and wound on a roll to obtain an ETFE1 film with a thickness of 50 μm and a width of 30 cm. The film was then cut into a 30 cm length and width in the flow direction.
[0060] (1-2) Preparation of aluminum alloy foil An aluminum alloy foil based on JIS H 4160:1994, alloy part number 8079, and thickness 40 μm was prepared so as to have a length and width of 30 cm.
[0061] (1-3) Preparation of the laminate The ETFE film 1 prepared in (1-1) was laminated on both sides of the aluminum alloy prepared in (1-2). In addition, a release film was laminated on the outside of both sides. The release film used was a polyimide film "Kapton" 200H / V, 50 μm thick, manufactured by Toray DuPont Co., Ltd. After lamination in this manner, the laminate was pressed using a vacuum press under conditions of a temperature of 240°C, a time of 15 minutes, and a pressure of 10 MPa, and then removed and cooled in a room temperature atmosphere for 5 minutes. After cooling, the release films on both sides were peeled off to obtain the laminate of Example 1.
[0062] [Example 2] (2-1) Preparation of ETFE film 2 In the same manner as in Example 3 of WO2015 / 182702, ETFE2 was polymerized in a ratio of TFE / E / HFP (hexafluoropropylene) / CH2=CH(CF2)4F / itaconic anhydride = 47.5 / 43.4 / 8.3 / 0.6 / 0.3 (mol%). The melt flow rate of ETFE2 was 11 mm 3 / sec, and the melting point was 183°C. ETFE2 was extruded using a single-screw extruder with a screw diameter of 30 mm at a barrel temperature of 220°C and a die temperature of 220°C to produce pellets. The pellets were extruded at a T-die temperature of 260°C using a single-screw extruder with a screw diameter of 30 mm, and wound on a roll to obtain an ETFE2 film with a thickness of 50 μm and a width of 30 cm. The film was then cut into a 30 cm length and width in the machine direction.
[0063] (2-2) Preparation of aluminum alloy foil An aluminum alloy foil was prepared in the same manner as in Example 1 (1-2).
[0064] (2-3) Preparation of the laminate An ETFE film 2 was placed on one side of the aluminum alloy prepared in (2-2), and a release film similar to that in Example 1 was further placed and laminated thereon. After lamination in this manner, pressing was performed using a vacuum press device under conditions of a temperature of 190°C, a time of 15 minutes, and a pressure of 10 MPa, and then the laminate was removed and cooled in a room temperature atmosphere for 5 minutes. Thereafter, the ETFE film 1 of Example 1 was placed on the other side of the aluminum foil, and the same release film as in Example 1 was further placed and laminated on top of that. After lamination in this manner, pressing was performed using a vacuum press device under conditions of a temperature of 240°C, a time of 15 minutes, and a pressure of 10 MPa, and then the laminate was removed and cooled in a room temperature atmosphere for 5 minutes. After cooling, the release films on both sides were peeled off to obtain a laminate of Example 2.
[0065] [Example 3] After preparing an aluminum alloy foil in the same manner as in (1-2) of Example 1, an ETFE film 2 was placed on both sides of the aluminum alloy, and a release film similar to that of Example 1 was further placed and laminated thereon. After lamination in this manner, the laminate was pressed using a vacuum press under conditions of a temperature of 190°C, a time of 15 minutes, and a pressure of 10 MPa, and then removed and cooled in a room temperature atmosphere for 5 minutes. After cooling, the release films on both sides were peeled off to obtain a laminate of Example 3.
[0066] [Example 4] (4-1) Preparation of PFA film 1 PFA1 was polymerized in the same manner as in Example 5 of WO2015 / 182702, with a ratio of TFE / CF2=CF-O-(CF2)3F / hymic anhydride=97.9 / 2.0 / 0.1 (mol%). The melting point of PFA1 was 305°C, and the melt flow rate was 11.0g / 10min. PFA1 was extruded at a die temperature of 340° C. using a 30 mmφ single-screw extruder equipped with a 750 mm wide coat hanger die, and taken up on a roll to obtain a 50 μm thick, 30 cm wide PFA film 1. The film was then cut into a 30 cm length and width in the flow direction.
[0067] (4-2) Preparation of aluminum alloy foil An aluminum alloy foil was prepared in the same manner as in Example 1 (1-2).
[0068] (4-3) Preparation of the laminate The PFA film 1 prepared in (4-1) was laminated on both sides of the aluminum alloy prepared in (4-2). Furthermore, the same release films as in Example 1 were laminated on both sides of the PFA film 1. After lamination in this manner, the laminate was pressed using a vacuum press under conditions of a temperature of 305°C, a time of 15 minutes, and a pressure of 1 MPa, and then removed and cooled in a room temperature atmosphere for 5 minutes. After cooling, the release films on both sides were peeled off to obtain a laminate of Example 4.
[0069] [Example 5] (5-1) Preparation of PFA film 2 A TFE / perfluoro(alkyl vinyl ether) copolymer (AGC, Fluon (registered trademark), PFA P-63P, melting point: 305°C, melt flow rate: 13.0 g / 10 min) was extruded at a die temperature of 340°C using a 30 mmφ single-screw extruder having a 750 mm wide coat hanger die, and taken up on a roll to obtain a PFA film 2 having a thickness of 50 μm and a width of 30 cm. Furthermore, the film was cut into a 30 cm length and width in the flow direction.
[0070] (5-2) Preparation of aluminum alloy foil An aluminum alloy foil was prepared in the same manner as in Example 1 (1-2).
[0071] (5-3) Preparation of the laminate PFA films 1 were placed on both sides of the aluminum alloy prepared in (5-2), and PFA films 2 and the same release films as in Example 1 were laminated in that order on the PFA films 1 on both sides. After lamination in this manner, the laminate was pressed using a vacuum press under conditions of a temperature of 305°C, a time of 15 minutes, and a pressure of 1 MPa, and then removed and cooled in a room temperature atmosphere for 5 minutes. After cooling, the release films on both sides were peeled off to obtain a laminate of Example 5 having a 5-layer structure.
[0072] [Example 6] (6-1) Preparation of polypropylene film A polypropylene film was prepared by coextrusion of a 5 μm thick maleic anhydride modified polypropylene layer and a 45 μm thick unmodified polypropylene layer.
[0073] (6-2) Preparation of aluminum alloy foil An aluminum alloy foil was prepared in the same manner as in Example 1 (1-2).
[0074] (6-3) Creating a laminate A polypropylene film was placed on one side of the aluminum alloy prepared in (6-2), and a release film similar to that in Example 1 was further placed and laminated. After lamination in this manner, pressing was performed using a vacuum press under conditions of a temperature of 140°C, a time of 15 minutes, and a pressure of 10 MPa, and then the product was removed and cooled in a room temperature atmosphere for 5 minutes. After cooling, the release films on both sides were peeled off to obtain an intermediate laminate. Then, a urethane resin adhesive was applied to the other side of the aluminum foil of the intermediate laminate using a gravure roll, and after drying to a certain extent by heating, a biaxially stretched nylon film having a thickness of 25 μm was laminated to the adhesive surface to obtain the laminate of Example 6.
[0075] [Example 7] A laminate of Example 7 was obtained in the same manner as in Example 1, except that the ETFE 1 film was replaced with the PFA film 2 obtained in Example 5, and the pressing conditions were a temperature of 305° C., a time of 15 minutes, and a pressure of 1 MPa.
[0076] [Example 8] A laminate of Example 8 was obtained in the same manner as in Example 5, except that a polyimide film "Kapton" 200H / V, 50 μm thick, manufactured by DuPont-Toray Co., Ltd., was used in place of the aluminum alloy foil.
[0077] [Example 9] A laminate of Example 9 was obtained in the same manner as in Example 6, except that a polyimide film "Kapton" 200H / V, 50 μm thick, manufactured by DuPont-Toray Co., Ltd., was used in place of the aluminum alloy foil.
[0078] <Evaluation> (1-1) Fabrication of all-solid-state batteries An all-solid-state battery cell having the following configuration was prepared, and the all-solid-state battery was wrapped in the laminate prepared above and then heat-sealed. Then, electrodes were attached to prepare an oxide-based all-solid-state battery.
[0079] [Table 1]
[0080] (1-2) Heat sealability We visually checked whether the heat seal was done. If it was possible, we gave it an A, and if it was not possible, we gave it an F.
[0081] (1-3) Delamination After sealing, the laminate itself was visually inspected for the occurrence of delamination. If no delamination was observed, it was rated as A, and if delamination was observed, it was rated as F.
[0082] (1-4) Charge / discharge test The sealed solid-state battery was placed in an oven set at 170°C and subjected to 100 continuous charge / discharge cycles. If charging and discharging were possible after 100 cycles, the battery was rated as A, and if charging and discharging were not possible, the battery was rated as F. If at least one of (1-2) heat sealability and (1-3) delamination was rated as F, the battery was rated as F without conducting the charging and discharging test.
[0083] (2) Water vapor permeability Based on JIS K7129-1:2019, the water vapor permeability was measured at 40℃ and RH90% using a differential pressure gas / water vapor permeability tester (GC method). Water vapor permeability is 0.005g / m 2 If the test satisfied the criteria of less than 100 days, the test was rated as A, and if not, the test was rated as F. If at least one of (1-2) heat sealability and (1-3) delamination was rated as F, the test was rated as F without measuring the water vapor transmission rate.
[0084] (3) Oxygen permeability Based on JIS K7126-2:2006, oxygen permeability was measured at 23°C using a differential pressure gas / water vapor permeability tester (GC method). Oxygen permeability is 0.005g·ml / m 2 If the test satisfied the criteria of less than 1000 / day atm, the test was rated as A, and if it did not, the test was rated as F. If at least one of (1-2) heat sealability and (1-3) delamination was rated as F, the test was rated as F without measuring the oxygen permeability.
[0085] [Table 2]
[0086] As shown in Table 2, the laminates of Examples 1 to 5, which have, in this order, a first fluororesin layer containing a fluororesin having an adhesive functional group, a metal layer having an average thickness of 5 to 300 μm, and a second fluororesin layer containing a fluororesin having an adhesive functional group, have excellent heat sealability, no peeling occurs between the layers of the laminate, and the all-solid-state battery can be charged and discharged even after 100 continuous charge-discharge cycles, and therefore have excellent heat resistance. It is also found that the laminates of Examples 1 to 5 have low oxygen permeability and water vapor permeability, and therefore have excellent barrier properties. These results show that the laminates of Examples 1 to 5 are excellent as exterior bodies for all-solid-state batteries and are also suitable as exterior bodies for batteries other than all-solid-state batteries. In addition, the laminates of Examples 1 to 5 are excellent in heat resistance and barrier properties, and therefore are also suitable for applications other than exterior bodies, such as diaphragm valves.
[0087] On the other hand, Example 6, which used polypropylene film and nylon film instead of a fluororesin having adhesive functional groups, had heat sealability and barrier properties and no delamination was observed, but it could not withstand 100 cycles of continuous charging and discharging. Figure 4 shows a photograph of the appearance after a charge-discharge test when the laminate of Example 6 was used as an exterior body. The laminate of Example 6 reached the state shown in the photograph of Figure 4 after 37 cycles, and the test was stopped. 5 shows a photograph of the appearance after a charge-discharge test when the laminate of Example 1 was used as an exterior body. The laminate of Example 1 showed no change in appearance even after 100 cycles.
[0088] Moreover, Example 7, in which a non-adhesive fluororesin was used, was inferior in all evaluation items. Example 8, in which a polyimide film was used instead of the aluminum alloy foil, had poor barrier properties. Example 9, in which a polypropylene film and a nylon film were used instead of a fluororesin having an adhesive functional group, and a polyimide film was used instead of an aluminum alloy foil, could not withstand 100 continuous charge / discharge cycles and also had poor barrier properties.
[0089] The disclosures of Japanese Patent Applications Nos. 2023-120103, 2023-194606, and 2024-34259 are incorporated by reference in their entireties into this disclosure. All publications, patent applications, and standards in this disclosure are incorporated by reference into this disclosure to the same extent as if each individual publication, patent application, or standard was specifically and individually indicated to be incorporated by reference. [Explanation of symbols]
[0090] 10, 20 laminate 12 First fluororesin layer 14 Metal layer 16 Second fluororesin layer 21 First outer layer 22 First fluororesin layer 24 metal layer 26 Second fluororesin layer 27 Second outer layer 30 Bag body 40 Solid state battery 42 All-solid-state battery cells 44 Positive terminal 46 Negative terminal
Claims
1. A laminate comprising, in this order, a first fluororesin layer containing a fluororesin having an adhesive functional group, a metal layer having an average thickness of 5 to 300 μm, and a second fluororesin layer containing a fluororesin having an adhesive functional group.
2. 2. The laminate according to claim 1, wherein the adhesive functional group is at least one selected from the group consisting of a carbonyl group-containing group, a hydroxy group, an epoxy group, an amide group, an amino group, an isocyanate group, a glycidyl group, a cyano group, a silyl group, and a silanate group.
3. 3. The laminate according to claim 1 or 2, wherein the fluororesin having an adhesive functional group in the first fluororesin layer and the second fluororesin layer each independently comprises at least one selected from the group consisting of a copolymer having a unit derived from ethylene, a unit derived from tetrafluoroethylene, and a unit derived from a monomer having the adhesive functional group, a copolymer having a unit derived from tetrafluoroethylene, a unit derived from perfluoro(alkyl vinyl ether), and a unit derived from a monomer having the adhesive functional group, a copolymer having a unit derived from vinylidene fluoride and a unit derived from a monomer having the adhesive functional group, and a copolymer having a unit derived from vinyl fluoride and a unit derived from a monomer having the adhesive functional group.
4. 3. The laminate according to claim 1 or 2, wherein the metal layer comprises at least one selected from the group consisting of aluminum, an aluminum alloy, stainless steel, copper, and steel.
5. 3. The laminate according to claim 1 or 2, further comprising an outer layer containing at least one resin selected from the group consisting of a fluororesin other than the fluororesin having an adhesive functional group, a polyimide, and a polyether ether ketone, on the outer side of at least one of the first fluororesin layer and the second fluororesin layer.
6. The laminate according to claim 5, wherein the other fluororesin comprises at least one selected from the group consisting of a copolymer having a unit derived from ethylene and a unit derived from tetrafluoroethylene, a copolymer having a unit derived from tetrafluoroethylene and a unit derived from perfluoro(alkyl vinyl ether), a polymer having a unit derived from vinylidene fluoride, and a polymer having a unit derived from vinyl fluoride.
7. The laminate according to claim 1 or 2, which is an exterior body for a battery.
8. The laminate according to claim 7 , which is an exterior body for an all-solid-state battery.
9. 3. The laminate of claim 1 or 2, which is a diaphragm valve.
10. A pouch for an all-solid-state battery, comprising one or more sheets of the laminate according to claim 1 or 2, at least a portion of a peripheral edge of which is heat-sealed.
11. An all-solid-state battery comprising: an all-solid-state battery cell; and the laminate according to claim 1 or 2 that exteriorly covers the all-solid-state battery cell.
12. A diaphragm pump having a diaphragm valve comprising the laminate according to claim 1 or 2.
Citation Information
Patent Citations
Diaphragm valve membrane and manufacture thereof
JP1986215050A
Packaging material for polymer battery
JP2011138793A
Packaging material for battery case and case for battery
JP2013065565A